Kajian Tentang Efek Pemberian Blondo Dalam Ransum Terhadap Performans Ayam Broiler - Husmaini Husmaini; M.H. Abbas; L.Y. Putri (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2007)
An experiment was conducted to studi the effect of the blondo in diet to the performance chicken. Five diets were formulated with different level blondo in diet i,e : (A) 0% , (B) 3%, (D) 6% , (D) 9 % and (E) 12 %. The diets were offered for 6 weeks to 80 broiler chickens 3 old days. Variable measured included : Feed consumption , body weight gain, FCR,  carcass and percentage of abdominal fat. The data were statistically analyzed for variance analysis in completely randomized design. The results indicated that 12 % blondo in diet gave significant effect to improved performance of broiler chickens.